Impact of tourism on regional economic growth a global value chain perspective - Liu, Anyu (Economics working papers)
The economic impact of tourism development on economies in the global value chain remains understudied. Applying the multiregional input–output model to Thailand, this paper examines the economic contribution of tourism to its economy and to the global economy. Results reveal a strong spillover effect and linkage with domestic industries but weak connections with external industries of economies in the global supply chain.